If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57 + -6 = 8x + 13 Combine like terms: 57 + -6 = 51 51 = 8x + 13 Reorder the terms: 51 = 13 + 8x Solving 51 = 13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 51 + -8x = 13 + 8x + -8x Combine like terms: 8x + -8x = 0 51 + -8x = 13 + 0 51 + -8x = 13 Add '-51' to each side of the equation. 51 + -51 + -8x = 13 + -51 Combine like terms: 51 + -51 = 0 0 + -8x = 13 + -51 -8x = 13 + -51 Combine like terms: 13 + -51 = -38 -8x = -38 Divide each side by '-8'. x = 4.75 Simplifying x = 4.75
| 132*17/4*4/9 | | 3x+7=77-4 | | -7+y=-27 | | -9x-3y=6 | | m^2+7m-51/4=0 | | (X^2+3x+4)=0 | | 4(1+108x)=5 | | (3x+1)(9x^2-4)=0 | | 9b^6+24b^3+16= | | 5x+8y=4y | | 2x^4+9x^2-5=0 | | 2x^3-1=0 | | 6m-3/2=9 | | 2pier=44 | | k+8k=28 | | 2x^2-0.5x=0 | | 3x^2+18=(3k+2)x | | 1/6+1/3+1/4 | | 65+3t=0 | | 2x^2-(2m-1)x-22=0 | | ln(3-x)=0 | | 17/18+2 | | 3x(1-5x)=0 | | 3x-5=17-x | | 1/9+5/6+2 | | (2x+1)(4-3x)=0 | | n+9=3+3n | | 48-4x=2x^2 | | 1/4(5x-1)=4 | | 9x+29=2x+106 | | (1/3)x+(1/4)=(5/12) | | 2x+9/x-3=7 |